Diplopia and Optic Disc Edema as the Ocular Manifestations of COVID-19 in a Seven-Year-Old Child - Anna Rzeszotarska; Marta Pawlak; Chmielarz-Czarnocińska Anna; Justyna Szczapa-Jagustyn; Jarosław Kocięcki; Joanna Siwiec-; Anna Gotz-Więckowska (Hindawi Limited, 2022)
Serious ocular complications due to SARS-CoV-2 disease in children are rare. Herein, we present a case report of a seven-year-old patient, who was diagnosed with pediatric inflammatory multisystem syndrome (PIMS) due to COVID-19 and developed the ocular manifestations comprising diplopia and binocular optic disc edema. The patient condition improved within few weeks without any ocular sequels so far.